Desempenho agronômico e digestibilidade ruminal de variedades de cana-de-açúcar cultivadas sob irrigação suplementar - LIMA , Allana Tereza Mesquita de (2020)
The objective of this study was to evaluate the agronomic characteristics, chemical composition and ruminal digestibility in situ of eight varieties of sugarcane (CV-4, RB041443, RB-855035, RB-867515, RB-92579, RB-931011, RB -951541 and RB-962962) grown under supplementary irrigation, with a view to feeding dairy cattle. The experiment was designed in randomized blocks with eight treatments and three replications, totaling 24 experimental plots. Biometric analyzes were performed 360 days after planting and 360 days after cutting, where the following were evaluated: stem length (CC), stem diameter (DC), number of green leaves (NFV) and leaf area (AF). The productivity in tons of stalks per hectare (TCH) and the concentration of soluble sugars in ºbrix were evaluated in cane-plant and cane-soca1. Stem samples of each variety were crushed and pre-dried in an oven to determine their chemical composition: dry matter (MS), mineral matter (MM), neutral detergent fiber (NDF), acid detergent fiber (FDA) and lignin (Lig). For the evaluation of ruminal digestibility in situ in 24h of DM and NDF, three Girolando cows, cannulated in the rumen, with an average weight of 510 ± 20 kg were used. Samples containing 5 g of pre-dry stem material and the entire plant of the cane-plant were weighed in bags of non-woven fabric (TNT) and incubated in the rumen of the animals. The ruminal digestibility of DM was calculated with the disappearance of DM in 24 hours of incubation, in proportion to the DM originally incubated and the DM residue after 72h of incubation (RES 72h). The data were submitted to analysis of variance by the F test and the means compared by the Tukey test at 5% probability, using the InfoStat 12.0 statistical software. The TCH of cane-plant did not show any difference between the varieties, with an average of 104.20 t ha -1 of stalks. There was no difference between the genotypes for the TCH of the cane, with an average of 155.8 t ha -1. There was no difference between varieties in terms of the average values of the stem stem bromatology, MS (27.34%), MM (1.52%), NDF (40.62%), FDA (22.28%) and LIG (3 , 50%). The chemical composition of sugarcane in whole plant showed differences (P <0.05) between varieties, in terms of DM (27.03%), MM (1.91%), NDF (39.59%), FDA (27.95%) and LIG (4.38%). The DEG MS after 24 hours of incubation for the whole stem parts was not different between the varieties, with an average of 46.20%, for the whole plant component there was a statistical difference (P <0.05) and the variety with superior performance was a RB92579 (65%) and the lowest performance was obtained by the varieties RB931011 (50%) and RB951541 (50.33%). The values of DEG NDF for whole stem ranged from 18.23 to 25.33% with an average of 21.25%, whereas for the whole plant variable from 18.6 to 24.3% with an average of 20.7%, in both the sugarcane parts the DEG FDN did not present statistical difference. Under supplementary irrigation, the eight sugarcane genotypes showed similarity in stalk productivity, brix values and ruminal digestibility in situ 24h of DM and NDF in plant cane.